In search of comity: TEI for distant reading - Lou Burnard; Christof Schöch; Carolin Odebrecht (Journal of the Text Encoding Initiative)
Any expansion of the TEI beyond its traditional user base involves a recognition that there are many differing answers to the traditional question “What is text, really?” We report on some work carried out in the context of the COST Action Distant Reading for European Literary History (CA16204), in particular on the TEI-conformant schemas developed for one of its principal deliverables: the European Literary Text Collection (ELTeC). The ELTeC will contain comparable corpora for each of at least a dozen European languages, each being a balanced sample of one hundred novels from the period 1840 to 1920, together with metadata concerning their production and reception. We hope that it will become a reliable basis for comparative work in data-driven textual analytics. The focus of the ELTeC encoding scheme is not to represent texts in all their original complexity, nor to duplicate the work of scholarly editors. Instead, we aim to facilitate a richer and better-informed distant reading than a transcription of lexical content alone would permit. At the same time, where the TEI encourages diversity, we enforce consistency by permitting representation of only a specific and quite small set of textual features, both structural and analytical. These constraints are expressed by a master TEI ODD, from which we derive three different schemas by ODD chaining, each associated with appropriate documentation.